Design of New Normal Health Protocol Reminder Using Arduino Nano and Ultrasonic Sensor - Dwi Hastuti; M. Rizqi Zulkarnain (BEST, 2021)
Corona virus is a group of viruses that can cause disease in animals or humans. The most common symptoms of COVID-19 are fever, dry cough and feeling tired. Other symptoms that some patients may experience less often include aches and pains, nasal congestion, headache, conjunctivitis, sore throat, diarrhea, loss of taste or smell, rash on the skin, or discoloration of fingers or toes. The Indonesian government urges the public to maintain productivity even in the midst of the ongoing corona virus pandemic with a new order called the new normal, namely by implementing health protocols. PGRI Adi Buana University Surabaya is one of the places where many people do their activities and gather. The existence of this gathering activity can increase the risk of transmitting COVID-19. To prevent transmission, every academic community must always apply the new normal health protocol as recommended by the government, such as wearing masks, washing hands with soap, and maintaining social distancing. So far, health protocol surveillance activities in the campus environment have only relied on the role of security so that it is less effective considering the limited human ability, so a tool is needed to always remind in implementing the new normal health protocol. The tool is in the form of audio using the Ultrasonic HC-SR04 and Arduino Nano sensors. So every object that passes through the sensor will be processed by a microcontroller (Arduino Nano) and then processed into an output in the form of a buzzer. The buzzer that comes out is a voice to remind everyone in the university to implement health protocols.